2014
DOI: 10.1111/jth.12570
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine restores trophoblast fusion affected by antiphospholipid antibodies

Abstract: Summary. Background: Obstetric antiphospholipid syndrome (APS) is defined by pregnancy complications associated with antiphospholipid antibodies (aPL). The mechanisms of the pathogenic effects of aPL in pregnancy are poorly understood. Toll-like receptors (TLR) have been implicated previously in APS. Objectives: The aims of our study were (1) to determine aPL effects on trophoblastic cell fusion and differentiation, (2) to identify which TLR is involved in this process, and (3) to evaluate the efficacy of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 38 publications
(78 reference statements)
3
43
0
Order By: Relevance
“…Hydroxychloroquine (HCQ) provides another option in refractory obstetric APS: its addition to standard treatment allowed a decrease in the rate of pregnancy wastage from 81 to 19% [33 & ]. Such clinical efficacy is consistent with its well known in-vitro properties: HCQ not only reduces aPL binding to syncytiotrophoblasts and restores the placental expression of AnnexinA5 [25 && ], but also downregulates TLR4 expression, thus preventing the antib2GPI antibody-induced impairment of trophoblast differentiation [34] and reverses aPL-induced inhibition of pro-migratory IL-6, thus enhancing trophoblast migration [35].…”
Section: Obstetric Antiphospholipid Syndromesupporting
confidence: 67%
“…Hydroxychloroquine (HCQ) provides another option in refractory obstetric APS: its addition to standard treatment allowed a decrease in the rate of pregnancy wastage from 81 to 19% [33 & ]. Such clinical efficacy is consistent with its well known in-vitro properties: HCQ not only reduces aPL binding to syncytiotrophoblasts and restores the placental expression of AnnexinA5 [25 && ], but also downregulates TLR4 expression, thus preventing the antib2GPI antibody-induced impairment of trophoblast differentiation [34] and reverses aPL-induced inhibition of pro-migratory IL-6, thus enhancing trophoblast migration [35].…”
Section: Obstetric Antiphospholipid Syndromesupporting
confidence: 67%
“…Compared with the rate of miscarriages among clinically recognized pregnancies in the general population (12-15%) (24,25), women with pSS are at a higher risk of miscarriage, with approximately 30% experiencing miscarriages in our study. Immunological disturbances may be associated with the mechanism of spontaneous abortion, but the present study did not allow us to evaluate the role of aPL antibodies (encountered in 22% of patients with pSS), which are involved in trophoblastic differentiation and invasion through Toll-like receptor 4 (TLR4) (26). However, the presence of aPL antibodies in pSS patients is not associated with the clinical events of APS (27,28).…”
Section: Discussionmentioning
confidence: 91%
“…However, the limited number of women examined (n = 6) limits our analysis of the potential positive impact of HCQ. Experimental models tend to show that HCQ counters the negative effects of aPL antibodies on trophoblastic differentiation through TLR4 (26). Other immunological disturbances associated with pSS may play a role in placentation and could be restored through immunomodulation therapies.…”
Section: Discussionmentioning
confidence: 98%
“…17 Also, it has been reported that hydroxychloroquine restores trophoblast fusion that is affected by aPL. 18 These studies suggest that hydroxychloroquine may improve pregnancy outcome in women with aPL, especially in those with recurrent pregnancy loss refractory to conventional treatment. 19 Several studies have assessed the effect of hydroxychloroquine on pregnancies in women with SLE and demonstrated that hydroxychloroquine is safe in pregnancy.…”
mentioning
confidence: 99%